The Digital Leap: A Phenomenological Inquiry into Culinary MSMEs Marketing in Malang - Afifa, Nurul Hildha; Pratikto, Heri; Dhewi, Titis Shinta (PT. EQUATOR SINAR AKADEMIA, 2025)
This research explores the phenomenon of digital marketing adoption by culinary MSMEs in Malang City using a transcendental phenomenological approach. The study aims to understand the implementation of digital marketing strategies, identify digitalization models, and analyze their impact on business development. Data were collected through observation, interviews, and documentation from five culinary MSMEs and analyzed using phenomenological techniques and SWOT analysis. The findings reveal that MSMEs have embraced various digital channels, such as social media, marketplaces, and food delivery platforms, to expand market reach and strengthen brand awareness. Positive perceptions of technology's usefulness and ease of use, as conceptualized in the Technology Acceptance Model (TAM), significantly influence adoption decisions. The research identifies diverse digitalization strategies tailored to the characteristics of each MSME and highlights the critical role of digital marketing in driving business growth, improving operational efficiency, and fostering adaptive business cultures. Based on the findings, the study proposes strategic recommendations to enhance digital competitiveness, emphasizing the need for digital literacy improvement and continuous innovation. This study enriches the scientific discourse on MSME digitalization and offers practical insights for business actors and policymakers in the culinary sector.